2012
DOI: 10.1002/lary.22474
|View full text |Cite
|
Sign up to set email alerts
|

Lateral oropharyngeal wall and supraglottic airway collapse associated with failure in sleep apnea surgery

Abstract: Objectives/Hypothesis To identify patterns of airway collapse during preoperative drug-induced sleep endoscopy (DISE) as predictors of surgical failure following multilevel airway surgery for patients with obstructive sleep apnea-hypopnea syndrome (OSAHS). Study Design Retrospective clinical chart review. Methods Medical records of patients who underwent site-specific surgical modification of the upper airway for treatment of OSHAS were reviewed. Patients were included in this study if they had a preoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
87
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 32 publications
2
87
5
Order By: Relevance
“…The reason for treatment failure using UPPP in these patients might be increased pharyngeal wall collapse. The study reported by Soares et al [16], that some of the patients with failed UPPP had got lower pharyngeal wall and supraglottic tissue collapse, was consistent with our speculation.…”
Section: Discussionsupporting
confidence: 92%
“…The reason for treatment failure using UPPP in these patients might be increased pharyngeal wall collapse. The study reported by Soares et al [16], that some of the patients with failed UPPP had got lower pharyngeal wall and supraglottic tissue collapse, was consistent with our speculation.…”
Section: Discussionsupporting
confidence: 92%
“…Lateral wall obstruction is considered to be the most dynamic structure of the upper airway and thus a major contributor of upper airway collapse in OSA patients. Soares and colleagues have shown that patients with lateral wall obstruction are associated with surgical failure [ 25 ]. Overall frequency of lateral wall collapse in our study was 70.6 % in the supine position which is higher than other reports with DISE (51.2 %) [ 18 ].…”
Section: Discussionmentioning
confidence: 41%
“…There is a strong association between lateral pharyngeal wall collapse and severity of oxygen desaturation during DISE [26]. Soares et al also reported the presence of severe lateral pharyngeal wall on preoperative DISE is associated with sleep surgical failure [27]. The most effective surgical treatment for OSA besides a tracheostomy is maxillomandibular advancement [28,29].…”
Section: Discussionmentioning
confidence: 97%